2016
DOI: 10.1159/000445581
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Reduced Epidural Fibrosis in Rat Models after Laminectomy via Downregulating EGR1

Abstract: Background/Aims: Epidural fibrosis, a common complication after laminectomy, has been demonstrated to be closely associated with poor surgical outcomes. Previous studies showed that taurine had remarkable anti-fibrotic effects on lung and liver fibrosis. We performed this study to investigate the effects of taurine in rat models of epidural fibrosis after laminectomy and to explore the potential molecular mechanism. Methods: Laminectomy was performed on each rat to establish epidural fibrosis model. After taur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…To figure out whether miR-21 promoted CFs fibrosis through suppressing Smad7 signaling, we further explored phosphorylation levels of Smad2 and Smad3, which have been demonstrated to be negatively regulated by Smad7 and play a central role in activation of fibroblasts [36]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To figure out whether miR-21 promoted CFs fibrosis through suppressing Smad7 signaling, we further explored phosphorylation levels of Smad2 and Smad3, which have been demonstrated to be negatively regulated by Smad7 and play a central role in activation of fibroblasts [36]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Su et al [74] observed that administration of taurine in cardiac patients induces a potent anti-inflammatory response in the form of decrease in serum IL-6 and an increase in serum IL-10 with significant improvement in arrhythmias. Another study of Yang et al highlighted the ability of taurine to reduce epidural fibrosis in rat models after laminectomy via downregulating early growth response protein 1 (EGR1), an enhancer of fibrosis, both in vivo and in vitro [75]. …”
Section: Discussionmentioning
confidence: 99%
“…Taurine, as an endogenous antioxidant and a scavenger of the hydroxyl radical, may play a part in treating toxicity mediated by oxygen radical [23]. Many studies have demonstrated that Taurine has several pharmacological and biological properties including antioxidant, anti-fibrotic and elicited retinal toxicity [24, 25]. In addition, study has been reported taurine can be involved in male reproductive organs [26] and act as an antioxidant of sperm [27].…”
Section: Introductionmentioning
confidence: 99%